The Application of Criminal Liability of PT. Simeulue Perkasa Sejahtera for Environmental Damage Due to Forest and Land Fires in Nagan Raya Regency - Nurlaili Maghfirah; Ridha Nur Ikhsan; Alfiadi; Zulfahmi (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
This research examines the criminal liability of PT. Simeulue Perkasa Sejahtera (PT. SPS) for environmental damage resulting from forest and land fires in Nagan Raya, Aceh. Utilizing a normative juridical approach, the study analyzes Indonesia’s legal framework, including Undang-Undang No. 32 Tahun 2009 on Environmental Protection and Management, Undang-Undang No. 41 Tahun 1999 on Forestry, and Peraturan Pemerintah No. 71 Tahun 2014 on Peat Ecosystem Protection. Findings indicate that although legal provisions impose strict liability on corporations for environmental harm, law enforcement remains weak and inconsistent. Evidence of fire hotspots within PT. SPS’s concession area failed to result in administrative or criminal sanctions, reflecting broader enforcement challenges such as lack of inter-agency coordination, inadequate forensic expertise, and judicial reluctance. The discussion highlights the importance of attributing liability not only to corporate entities but also to individual actors within the company. Furthermore, the study emphasizes the need for stronger administrative actions and judicial reforms to bridge the gap between law and practice. This research contributes to the discourse on corporate environmental accountability in Indonesia and calls for urgent legal and institutional reforms to ensure environmental justice and uphold international commitments related to climate change and transboundary haze pollution.